Atarama-Rojas, T. (2023). La audiencia social en la narrativa transmedia de Marvel - Feijoo Fernández, Beatriz (2023)
This book has its origins in the personal interest of a researcher in reflecting and discussing the scope and significance of transmedia narratives in people's daily lives. Starting from a specific case, but with global reach, the Marvel phenomenon, we meditate on the contribution made by the viewer, the prosumer, the fan to the fictional universe, not only in the form of isolated content, but also in the generation of meeting points. In them, a sense of consumed history is shared, but also of life in general, which ultimately contributes to the creation of a more human and integrated community.